Possibilities of Cr, Cu, Ni, Zn bioleaching from wastewater from mechanical and biological waste treatment installations - Kamizela, Tomasz; Kowalczyk, Mariusz (Instal, 2022)
The aim of the research was to determine the possibility of using bioleaching bacteria in the solubilization of heavy metals from wastewater generated in the installation of mechanical and biological waste treatment. The evaluation of the effectiveness of bioleaching was based on the monitoring of pH, redox potential and the concentrations of chromium, copper, nickel and zinc. The process of metal release to a dissolved form was a selective process depending on the characteristics of the collected wastewater and the process time. Moreover, in order, acidification of the wastewater, inoculation with microorganisms and the addition of sulfur as an energy substrate were the factors influencing the efficiency of bioleaching. The use of the most favorable process conditions enabled the solubilization of metals in the range of 70 – 95%. The use of the bioleaching process in wastewater treatment was limited due to variable process effects. The issue of processing this type of wastewater by bioleaching still seems to be prospective, the more so that the obtained biomass may constitute an added value of the processing technology as a fertilizer product.
Keywords: bioleaching; wastewater; mechanical – biological treatment of waste